(untitled) (Research, Society and Development, 2025)
Sodium–glucose cotransporter 2 (SGLT2) inhibitors have demonstrated cardiovascular benefits that extend beyond glycemic control, particularly in the context of coronary artery disease (CAD). This article synthesizes mechanistic and clinical evidence on SGLT2 inhibitors in coronary artery disease (CAD), with emphasis on inflammation, endothelial function, mitochondrial homeostasis, oxidative stress, and cardiac remodeling. A narrative literature review was conducted using the PubMed/MEDLINE, Embase, and Scopus databases (2015–2025), including experimental studies (in vitro/in vivo), clinical trials, and cohort studies published in Portuguese, English, or Spanish. Case reports and studies with insufficient clinical information were excluded. No protocol was registered; PRISMA and formal risk-of-bias assessment were not applied. Findings were organized thematically (molecular mechanisms; inflammation/endothelium; mitochondria; oxidative stress; clinical relevance to CAD). SGLT2 inhibitors lower pro-inflammatory mediators (e.g., TNF-α, IL-6, IL-1β), inhibit NLRP3 inflammasome activation, and favor M2 macrophage polarization. They preserve endothelial integrity—via AMPKα1/ULK1/FUNDC1-dependent mitophagy, reduced ROS, and increased NO bioavailability—and modulate cardiomyocyte metabolism, impacting infarct size and remodeling in experimental models. Clinically, the evidence supports extraglycemic benefits, particularly in patients with type 2 diabetes mellitus (T2DM) and cardiovascular risk. Convergent anti-inflammatory, antioxidant, and endothelial/mitochondrial effects support an adjunctive role of SGLT2 inhibitors in high-risk CAD profiles, while underscoring the need for randomized trials targeting CAD/MI-specific outcomes.